Inequalities in access to education and healthcare - Nunn, J.; Freeman, R.; Anderson, E.; Carneiro, L. C.; Carneiro, M. S. A.; Formicola, A.; Frezel, R.; Kayitenkore, J.; Luhanga, C.; Molina, G.; Morio, I.; Nartey, N. O.; et al. (Wiley-Blackwell Publishing, Inc, 2008)
The burden of disease is borne by those who suffer as patients but also by society at large, including health service providers. That burden is felt most severely in parts of the world where there is no infrastructure, or foreseeable prospects of any, to change the status quo without external support. Poverty, disease and inequality pervade all the activities of daily living in low-income regions and are inextricably linked. External interventions may not be the most appropriate way to impact on this positively in all circumstances, but targeted programmes to build social capital, within and by countries, are more likely to be sustainable. By these means, basic oral healthcare, underpinned by the primary healthcare approach, can be delivered to more equitably address needs and demands. Education is fundamental to building knowledge-based economies but is often lacking in such regions even at primary and secondary level. Provision of private education at tertiary level may also introduce its own inequities. Access to distance learning and community-based practice opens opportunities and is more likely to encourage graduates to work in similar areas. Recruitment of faculty from minority groups provides role models for students from similar backgrounds but all faculty staff must be involved in supporting and mentoring students from marginalized groups to ensure their retention. The developed world has to act responsibly in two crucial areas: first, not to exacerbate the shortage of skilled educators and healthcare workers in emerging economies by recruiting their staff; second, they must offer educational opportunities at an economic rate. Governments need to lead on developing initiatives to attract, support and retain a competent workforce.
Keywords: access; education; inequalities; oral health